The Wheat Exported from Israel to Tyre - Aikhler, Raʿanan (Vetus Testamentum, 2025)
The Hebrew Bible contains three references to the export of wheat from Israel to Tyre. Difficult and suspiciously similar phrases occur in the Masoretic Text of each: ḥiṭiym makholet in 1 Kgs 5:25 (Eng. 5:11); ḥiṭiym makṿot in the parallel 2 Chr 2:9 (Eng. 2:10); and ḥiṭey miniyt in Ezek 27:17. Moreover, in each passage, the ancient translations reflect further variant readings. This paper integrates textual criticism with information on wheat in antiquity in order to clarify all three passages. The paper may contribute to our understanding of international trade in the first half of the first millennium BCE.